Embroidered Stances as Craftivism and Ecoculture - Huhmarniemi, Maria; Hernandez Cervantes, Fabiola; Kravtsov, Tatiana; Kovero, Minna; Luiro, Elina (Lapin yliopisto, 2024)
The Embroidered Stances art collective revitalised traditional Nordic wool embroidery through the lens of craftivism. A collective of 14 artists, crafters, activists, and artist-researchers used wool fabric and naturally hand-dyed wool yarn and showed the embroideries as an exhibition.